EXPORT COMPETITIVENESS OF YARN COMMODITIES AND TEXTILE INDUSTRIES OF CENTRAL JAVA IN THE WORLD MARKET - Ikasari, Hertiana Ikasari (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2013)
Yarn commodities and textiles industries are the main export commodities of CentralJava. Nevertheless, there are still some problems. The purpose of this study was toanalyze the market share advantages and competitive position of yarn commoditiesand textile industries of Central Java in the world market. Acceleration Ratio (AR)and Trade Specialization Index (TSI) wereused to analyze the export competitivenessof yarn commodities and textile industries. The results obtained indicate that ARofthe exportof yarn commodities and textile industries in Central Java was greaterthan 1 (AR> 1). TSI of yarn commodities and textile industries in Central Java was0.45 and had positive value. These results indicate that Central Java has a strongmarket share and likely to be a regional exporter of yarns and textile commodities inthe world market.